Pharmacological relevance of primitive leafy Cactuses Pereskia - M., Sharif K.; Rahman, Md. Mokhlesur; Sarker, Md. Zaidul Islam; Azmir, Jannatul; Akanda, Jahurul Haque; A., Mohamed; S. H., Shamsudin; Samsudin, Siti Hadijah (BioTek Journal, India, 2013)
Pereskia is the only cactus genus that has green leaf unlike other genera of large Cactaceae family. Pereskia is well known in scientific community for their heterogeneous, morphological and botanical characteristics. Although Pereskia genus originates in Latin American countries but it is also widespread in tropical areas like Malaysia, Indonesia. Some species of Pereskia have been used by traditional practitioners for the treatment of many diseases such as cancer, high blood pressure, diabetes, gastric pain and ulcer. Some of the species of this genus have been proven to possess diverse biological activities including anti-inflammatory, anti-microbial, antifungal, anti-nociceptive, anti-oxident and anti-cancer activities by several scientific investigations. The objective of this paper is to review the pharmacological activity and phytochemical properties of the Pereskia genus.